HUBUNGAN PENGETAHUAN DAN SIKAP PENDERITA TB PARU DENGAN KEPATUHAN MINUM OBAT ANTI TUBERKULOSIS DI PUSKESMAS KOMBOS - Sali M. Papeti; Dewi Suharto (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2022)
Pulmonary TB is an airborne infectious disease that mostly attacks the lungs. Knowledge is information that is captured by the five human senses, then developed through language and ways of thinking. Noncompliance and lack of understanding of the community in the use of drugs is one of the causes of therapy failure. Providing knowledge and understanding of patients in the use of drugs will have an impact on medication adherence and success in using drugs for therapy. The purpose of this study was to determine the relationship between knowledge and attitudes of pulmonary TB patients with adherence to taking anti-tuberculosis drugs at the Kombos Health Center Manado City. This study uses an analytical descriptive research design with a cross-sectional approach. The sampling technique in this study used a sampling technique using total sampling with a total of 42 respondents. The data collection technique was carried out using a questionnaire and using the Chi-Square test with a significance level of a = 0.05. The results of the study respondents had a low level of knowledge on medication adherence with a p value = 0.00, and had a low attitude towards medication adherence with a p value = 0.032. The conclusion of this study is that there is a relationship between knowledge and attitudes of pulmonary TB patients with adherence to taking anti-tuberculosis drugs at the Kombos Health Center Manado City.